Survival Benefits for Pulmonary Adenocarcinoma With Malignant Pleural Effusion After Thoracoscopic Surgical Treatment: A Real-World Study - Li, Xin; Li, Mingbiao; Lv, Jinshuang; Liu, Jinghao; Dong, Ming; Xia, Chunqiu; Zhao, Honglin; Xu, Song; Wei, Sen; Song, Zuoqing; Chen, Gang; Liu, Hongyu; et al. (Frontiers in Oncology, 2022)
Objectives: Malignant cells in the pleural fluid or pleural metastasis are classified as stage IV non-small cell lung cancer. Radical surgery is generally considered not suitable for such patients. The aim of our study was to discuss the effectiveness of video-assisted thoracoscopic surgery (VATS) in such patients. Methods: A retrospective analysis of the clinical records of 195 patients was performed. These patients were all diagnosed with locally advanced pulmonary adenocarcinomas with malignant pleural effusion (MPE, M1a) but no distant organ metastasis. The 195 patients included 96 patients who underwent VATS plus chemotherapy and 99 patients who received thoracic drainage plus chemotherapy. The baseline characteristics of the patients included age, gender, smoking history, Eastern Cooperative Oncology Group (ECOG) score, and number of chemotherapy cycles (2–4 cycles or >4 cycles); we also analyzed clinical characteristics including the specific surgical options of the VATS group. Results: In multivariate analysis, when compared to the thoracic drainage group, the VATS group remained significantly associated with the overall survival (HR=0.480 [95%CI 0.301-0.765]); when compared to the lobectomy, the sub-lobectomy and the palliative surgery, remained significantly associated with the overall survival (HR=0.637 [95%CI 0.409-0.993] and HR=0.548 [95%CI 0.435-0.832], respectively). The median survival time (MST) of patients who underwent VATS (n = 96, 49.2%) was 25 months (95% CI 22.373–27.627) whereas the patients who received thoracic drainage (n = 99, 50.8%) was 11 months (95% CI 9.978–12.022). For patients who underwent VATS, the MST of patients who received a lobectomy (n = 50, 52.1%) was 27 months (95% CI 22.432–31.568), the MST of patients who received a sub-lobectomy plus pleurodesis (n = 26, 27.1%) was 27 months (95% CI 19.157–34.843), and the MST of patients who received only pleurodesis (n = 20, 20.8%) was 12 months (95% CI 7.617–16.383). Conclusion: For pulmonary adenocarcinomas with MPE, receiving a lobectomy or sub-lobectomy plus pleurodesis with VATS was associated with improved survival compared with patients who only received thoracic drainage and chemotherapy. Our results and previously published data may justify the use of VATS for treating pulmonary adenocarcinomas with MPE.